Thank Heavens for Complainers: Impact of Effective Service Recovery on Customer Satisfaction and Post behavioral Intention in Malaysian Banking Industry - Goh, Guann Tyng (2012)
The commercial banks are among the service organizations that face intense competition all over the world. The competition has permitted customers to behave in a more demanding manner in their dealings with service providers since there are plenty of choices available in the market. In response, banks are implementing plans and strategies which can enhance customer satisfaction and post-behavioral intention through improved service quality. Unfortunately, service failures are unavoidable even for the best bank. Thus, an effective service recovery, the successful actions a service provider engages in response to a service breakdown, could result in the difference between customer retention and defection. In brief, this research aims to contribute to a growing body of service recovery knowledge by examining the relative impact of service recovery (perceived justice) on customer satisfaction as well as the relationships between customer satisfaction and post-behavioral intention (perceived trust, word of mouth and continue of service intention) in Malaysian commercial banking environment. Based on the research findings from 300 respondents, the impact of perceived interactional justice on customer satisfaction appears to be stronger than that of perceived procedural justice or perceived distributive justice. The findings also indicate that the effect of customer satisfaction on perceived trust is significant and positive. Lastly, the significant and positive effect of customer satisfaction on word of mouth as well as continue of service intention confirms again service recovery attempts after a service failure could ultimately enhance the post-behavioral intention of customers.